2016
DOI: 10.1111/sms.12712
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying levels of function between different subgroups of chronic ankle instability

Abstract: The purpose of this original investigation was to determine if selected sensorimotor, mechanical, and self-reported measures are different among chronic ankle instability (CAI) subgroups, healthy control participants, and lateral ankle sprain copers (LAS-Copers). Ninety-four participants volunteered and were categorized into perceived ankle instability (PI) alone (n = 13), recurrent ankle sprains (RAS) alone (n = 12), PI in combination with RAS (PI-RAS; n = 25), LAS-Copers (n = 18), and controls (n = 26). Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Abstracts of the remaining 42 studies were further screened, causing an additional 26 studies to be excluded. The full-text screening performed over the remaining 19 studies determined 17 studies for final inclusion [27,28,32,33,34,35,36,38,39,40,44,52,53,54,55,56,57], with two studies [31,58] excluded because they reported the same subject data as two other studies that were already included [52,53]. No additional studies were identified based on the references in previously included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Abstracts of the remaining 42 studies were further screened, causing an additional 26 studies to be excluded. The full-text screening performed over the remaining 19 studies determined 17 studies for final inclusion [27,28,32,33,34,35,36,38,39,40,44,52,53,54,55,56,57], with two studies [31,58] excluded because they reported the same subject data as two other studies that were already included [52,53]. No additional studies were identified based on the references in previously included studies.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only 2 studies thus far have reported more than one between-group comparison. In the study by Terada et al [14], patients were not grouped according to defined CAI criteria, and in the study by Brown et al [32], the main outcome was motion pattern, and the authors used only the Foot and Ankle Disability Index (FADI) to compare functional status between people with FAI or MAI and ankle copers. These authors [32] found that FADI scores in the MAI group were significantly lower than in the FAI and coper groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to our search for previous publications, only one study investigated HRQOL in patients with different types of CAI, but who were not categorized based on defined criteria for CAI [14]. In other words, no study thus far, to the best of our knowledge, has been conducted with patient-oriented tools to compare HRQOL and its various aspects (including physical performance and fear of re-injury) between different CAI subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, we are the first to examine RVTTS in individuals with and those without CAI under the inclusion guidelines outlined by the IAC, [1][2][3] which allow participants with fewer episodes of giving way, feelings of instability, and recurrent sprains compared with previous studies. 13,16 Although the intent of the guidelines was to establish homogeneity in CAI cohorts, previous researchers 32,33 who identified different functional impairments among subcategories of CAI patients supported the existence of heterogeneity within CAI. Our results and those of others 17 may provide evidence that greater group heterogeneity can result in an absence of RVTTS differences between CAI and LAS coper groups.…”
Section: Discussionmentioning
confidence: 99%